2016
DOI: 10.3390/ijerph13111085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Di-(2-ethylhexyl) Phthalate on Lipid Metabolism by the JAK/STAT Pathway in Rats

Abstract: The most widely used plasticizer, di-(2-ethylhexyl) phthalate (DEHP), is known to affect lipid metabolism and adipogenesis. We studied the effects of dietary DEHP exposure on metabolism in rats as well as the role of the JAK/STAT pathway in this process. Eighty rats were exposed to DEHP (0, 5, 50 and 500 mg/kg/d) through dietary intake for 4 weeks. We then collected blood samples, liver, and adipose tissues to detect modifications in the levels of serum lipids, leptin, adiponectin and insulin. JAK3, STAT5a and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 43 publications
4
26
0
Order By: Relevance
“…In most cases, JAKs depend on STATs to modulate physiologic processes (10)(11)(12)(13)(14); therefore, STAT proteins may also play important roles in the transcriptional control of adipogenesis (60). Studies in subcutaneous human primary adipocytes confirmed the up-regulation of STAT3 and STAT5 during differentiation (61).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In most cases, JAKs depend on STATs to modulate physiologic processes (10)(11)(12)(13)(14); therefore, STAT proteins may also play important roles in the transcriptional control of adipogenesis (60). Studies in subcutaneous human primary adipocytes confirmed the up-regulation of STAT3 and STAT5 during differentiation (61).…”
Section: Discussionmentioning
confidence: 96%
“…The JAK/STAT pathway plays an important role in mediating cell fates, such as apoptosis, differentiation, and proliferation (10)(11)(12)(13)(14). The suppression of JAK/STAT signaling causes stochastic and ectopic neural stem cell differentiation in vivo, suggesting an evolutionarily conserved function of JAK/STAT to regulate the robustness of stem cell differentiation (57).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies demonstrated that DEHP is hepatocarcinogen in rodent species and related this effect to the peroxisome proliferator activated receptor activation α and behave as prototypical peroxisome proliferators . Other studies demonstrated that DEHP alters lipid metabolism in rat liver through the inhibition of the Janus Kinase/Signal Transduction and Activator of Transcription (JAK/STAT) pathway leading to an accumulation of triglycerides and thus to obesity . We have already gathered several evidences suggesting that DEHP is genotoxic in the liver by induction of DNA damage and activate the p53‐dependent apoptotic pathway in vivo and in vitro .…”
Section: Introductionmentioning
confidence: 99%